Deposit Insurance Design and Implementation : Policy Lessons from Research and Practice - Demirgüç-Kunt, Asli; Kane, Edward J.; Laeven, Luc (World Bank, Washington, DC, 2012)
This paper illustrates the trends in deposit insurance adoption. It discusses the cross-country differences in design, and synthesizes the policy messages from cross-country empirical work as well as individual country experiences. The paper develops practical lessons from this work and distills the evidence into a set of principles of good design. Cross-country empirical research and individual-country experience confirm that, for at least the time being, officials in many countries would do well to delay the installation of a deposit insurance system.